Efektivitas metode pengajaran kitab kuning fathul qarib dalam pembelajaran fiqih di ponpes agro nuur el falah - Khaq, M. Burhanul (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2023)
This research aims to increase the effectiveness of the Fathul Qarib yellow book teaching method in learning fiqh at the Agro Nuur El Falah Islamic Boarding School. The yellow book Fathul Qarib was chosen as the main focus because it is one of the primary sources in Islamic studies which has long been used in various traditional Islamic boarding schools. The teaching methods applied include an interactive and participatory approach, using group discussion techniques, critical analysis of texts, and the application of fiqh concepts in the context of everyday life. This research involved participants from the students of the Agro Nuur El Falah Islamic Boarding School who were involved in a fiqh learning program using the yellow book Fathul Qarib. Data was collected through observation, interviews and questionnaires for students' understanding and acceptance of this teaching method. Data analysis was carried out using a qualitative approach to measure the effectiveness of learning methods. The results of the research show that the Fathul Qarib yellow book teaching method significantly increases the understanding of Islamic jurisprudence and the involvement of students in learning. It was also found that the interactive and participatory approach encouraged positive criticism of fiqh concepts, as well as facilitating the integration of Islamic values ​​in everyday life. This research contributes to the development of fiqh learning methods in Islamic boarding schools by exploring the potential of the yellow book Fathul Qarib as an effective teaching resource. The implications of this research can be a guide for Islamic educational institutions in improving the quality of learning and understanding of fiqh concepts among students.